2011
DOI: 10.4236/nr.2011.22013
|View full text |Cite
|
Sign up to set email alerts
|

Tannin–Phenol Formaldehyde Resins As Binders for Cellulosic Fibers: Mechanical Properties

Abstract: In this study Eucalyptus tannin (T) was isolated from outer bark of Eucalyptus trees; as sodium phenoxide salt and used as extender or copolymer into phenol formaldehyde (PF) resin at five percent (10, 20, 30, 40 and 50)% W/W. Tannin-phenol formaldehyde (TPF) and tannin formaldehyde-phenol formaldehyde (TFPF) resins that synthesized in this study were evaluated as adhesive material for cellulosic fibers by study the mechanical properties of the composite sheets. The results show that the substituting of (PF) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
1
5
0
3
Order By: Relevance
“…Dimensional stability and resistance against biodegradation were found to increase for cedar wood coated with phenol-formaldehyde resin [81]. Cellulose fibers coated similarly with plant tannin-based PF resin exhibited increased tensile strength [82]. Cashew nut shell liquid (CNSL), a natural, plant-based polymer of cardanol, cardol and anacardic acid monomer units, has been condensation polymerized and impregnated into alkali-treated sisal fibers and heated to form composites with high tensile strength and resistant to photodegradation [83].…”
Section: Coating or Blockingmentioning
confidence: 99%
“…Dimensional stability and resistance against biodegradation were found to increase for cedar wood coated with phenol-formaldehyde resin [81]. Cellulose fibers coated similarly with plant tannin-based PF resin exhibited increased tensile strength [82]. Cashew nut shell liquid (CNSL), a natural, plant-based polymer of cardanol, cardol and anacardic acid monomer units, has been condensation polymerized and impregnated into alkali-treated sisal fibers and heated to form composites with high tensile strength and resistant to photodegradation [83].…”
Section: Coating or Blockingmentioning
confidence: 99%
“…Perekat PF dan RF bersifat thermosetting waterproof dan sehingga sesuai untuk tujuan eksterior. Keunggulan perekat RF dibandingkan PF adalah suhu untuk curing /hardening lebih rendah (Hussein, Ibrahim, & Abdulla, 2011). mpelajari hardboard Tulisan ini me kualitas menggunakan bahan serat alternatif dua jenis dari bamb tali dan ampel u, yaitu jenis bambu dan mengidentifikasi karakteristik sifat (sifat dasar dan fisis mekanis ) produk papan serat dari masingmasing bambu untuk mengetahui kesesuaian dua jenis bambu tersebut sebagai bahan baku papan serat.…”
Section: Pendahuluanunclassified
“…Perbedaan proporsi campuran serat (pulp (Santoso, 2011;et al, Hussein, 2011). Akibatnya, setelah TRF mengeras, sifat higroskopis serat menurun dan kestabilan dimensi hardboard meningkat.…”
Section: Kadar Air Pengembangan Tebal Dan Penyerapan Airunclassified
See 1 more Smart Citation
“…Authors have reported on the development of biodegradable materials [6] [11]. Several other natural adhesives were developed using derivatives of plants and authors have analyzed the tannin structures used in the composition of adhesives [12]- [18]. Other authors have analyzed the use of tannin-based additives for thermal stabilization in bonding applications [19] [20] [21].…”
Section: Introductionmentioning
confidence: 99%